Building a Better International NGO: Greater than the Sum of the Parts? - and Crowley, James; Ryan, Morgana (Kumarian Press, 2013)
In the wake of tremendous growth in the size and scope of their activities, as well as the increased complexity of their programs, how can large international NGOs work effectively—so that the whole is greater than the sum of the parts? James Crowley and Morgana Ryan address this question, drawing on their extensive hands-on experience to offer a practical and even provocative guide. The authors cover a range of essential topics, among them: What are INGOs good at? What should they be good at? Where does new technology fit in? What about accountability? What’s the best way to tackle strategic planning? In the process, they challenge those in leadership positions to recognize and implement the changes that are needed so that their organizations can perform better—and stay relevant—in the decades to come.